The effect of inquiry combined science-technology-society (STS) learning to enhance critical thinking skills on science - Ita Ainun Jariyah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
One of the important skills to be mastered in the era of globalization is the critical thinking skills. This research is to determine the average increase of critical thinking skills of learners before and after implementing inquiry learning combined STS, and to know learner response about inquiry learning combined STS. This research was a “pre-experimental design” by design “the group pretest posttest design”. Samples were taken from the students of class VII SMPN 3 Peterongan. Data Collection was done by testing: pretest, posttest and questionnaire response of learners. Pretest and posttest data were analyzed by using paired t-test statistic. Questionnaire response of learners data were analyzed by using a percentage formula. The results of paired t test were 0.00 which was less than 0.05. The conclusion was there are differences in the results of critical thinking skills before and after implementation of inquiry-based teaching materials combined STS. Based on the results of the questionnaire response of learners found that learners gave positive response to the inquiry learning process combined STS.